PENGARUH MODEL PEMBELAJARAN KOOPERARIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATA KULIAH ASSESMEN PEMBELAJARAN MATEMATIKA - Stefania Baptis Seto; Maria Fatima Mei; Gregorius Taga (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The purpose of this research is to improve learning outcomes of mathematics learning assessment courses using the jigsaw-type cooperative learning model. The subjects in this study were students of the mathematics education study program at the University of Flores totaling 30 students using a classroom action research design (CAR). The results showed that the increase in learning outcomes of students' mathematics learning assessment courses in the first cycle obtained a percentage of 73.33% and was in the sufficient category and there were still 8 students whose scores were still below the KKM standard. Based on the results of observations, student activities have increased because they have started to understand learning using the Jigsaw cooperative model. And the increase in lecturer activity based on the results of observations has increased from cycle I to cycle II.